Determination of vapor pressure and thermal decomposition using thermogravimetrical analysis - Heym, F.; Korth, W.; Etzold, Bastian; Kern, C.; Jess, A. (Thermochimica Acta, 2015)
Vapor pressure and thermal stability of substances are important material properties with regard to industrial application. For high boiling samples their determination is laborious, and discrimination between evaporation and thermal decomposition is difficult. In this work, a general procedure is presented to determine the parameters of thermal decomposition as well as evaporation by thermogravimetrical analysis (TGA) at ambient pressure and high vacuum. In this context, the results of TG-experiments with two ionic liquids [EMIM][Ntf2] and [EMIM][MeSO3] are analyzed. Based on the kinetics of thermal decomposition, the concept of maximum allowable operation temperature is proposed and discussed as an alternative to the onset-temperature.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Ionic liquids; Maximum operation temperature; TGA; Thermal decomposition; Thermobalance; Vapor pressure